2017
DOI: 10.1073/pnas.1702493114
|View full text |Cite
|
Sign up to set email alerts
|

Speaker gaze increases information coupling between infant and adult brains

Abstract: SignificanceDuring communication, social ostensive signals (like gaze) are exchanged in a temporally contingent manner. Synchronized behavior creates social connectedness within human dyads, and even infants synchronize behaviorally with adults. However, the neural mechanisms that support infant–adult synchronization are unknown. Here, we provide evidence that infants up-regulate neural synchronization with adult partners when offered direct ostensive gaze, as compared with gaze aversion. Gaze therefore brings… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
245
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(299 citation statements)
references
References 43 publications
14
245
3
3
Order By: Relevance
“…They are also consistent with the views of social cognition researchers who have described gaze guidance as one of the most salient ostensive signals in human communication for conveying communicative intent (Csibra & Gergely, 2009;Leong et al, 2017 style that focuses more on social interaction and mutual relationships, whereas learners with a low level of social presence might apply a task-oriented processing style with a focus on goal achievement (Cohen, Solomon, Maxfield, Pyszczynski, & Greenberg, 2004;Tabernero, Chambel, Curral, & Arana, 2009). In our study, the learners with a higher level of social presence were sensitive to social interactivity in the learning environment and tended to follow the teacher's gaze guidance to the key information.…”
Section: Discussionsupporting
confidence: 85%
“…They are also consistent with the views of social cognition researchers who have described gaze guidance as one of the most salient ostensive signals in human communication for conveying communicative intent (Csibra & Gergely, 2009;Leong et al, 2017 style that focuses more on social interaction and mutual relationships, whereas learners with a low level of social presence might apply a task-oriented processing style with a focus on goal achievement (Cohen, Solomon, Maxfield, Pyszczynski, & Greenberg, 2004;Tabernero, Chambel, Curral, & Arana, 2009). In our study, the learners with a higher level of social presence were sensitive to social interactivity in the learning environment and tended to follow the teacher's gaze guidance to the key information.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, Leong et al. () recently demonstrated that a direct gaze resulted in stronger bidirectional adult–infant neural connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…At the age of 2 months, emotional expressions are coordinated with visual attention, and interactions including sequences of shared smiles emerge in parent–infant dyads (Feldman, ). An interesting recent finding showing that direct gaze strengthens bidirectional adult–infant neural connectivity during communication (Leong et al., ) raises the question of whether the shared smile with simultaneous eye contact might have a role of its own in early interaction.…”
Section: Introductionmentioning
confidence: 99%
“…were observed; during live interactions, bi-directional influences (adult→infant and infant→adult) were documented (Leong et al, 2017).…”
Section: Procedures 2 Which Directly Compared the Transitions Betweenmentioning
confidence: 99%